Challenges and progress of grouper aquaculture in asia: A Review - Cirilo O. Ybanez Jr.; Ruby C. Gonzales (Davao Research Journal)
Asia is widely recognized for its grouper aquaculture. China (65%), Taiwan (17%), and Indonesia (11%) together account for 93% of global grouper production. This study recorded 48 species, and 16 hybrids were used in Asian aquaculture. The conservation status of cultured grouper species is 67% least concern, 17% data deficient, 10% vulnerable, and 2% critically endangered, endangered, and near threatened. Most Asian countries face issues such as (1) lack of hatcheries, (2) poor seed stock, (3) poor broodstock quality, (4) lack of financial and technical support, (5) trash fish and accessibility to fish pellets, (6) poor water quality, (7) diseases, and (8) capture-based aquaculture. These issues, combined with overfishing, contribute to a decline in grouper productivity and their wild population. The decline has alarmed experts and conservationists looking into the causes and potential remedies to this problem. Some management strategies mentioned in this paper include: (1) closed season during spawning aggregation, (2) establishing more marine protected areas (MPAs), particularly the no-take marine reserve, (3) non-consumptive utilization of groupers (eco-tourism) and (4) establishing more full-cycle grouper aquaculture. The results of this study suggest that implementing these strategies could be an effective means of addressing the issue of grouper production and that additional research is required to determine the most effective method of addressing this problem. The findings of this study have significant implications for the development and sustainability of grouper aquaculture and highlight the need for further research in this area.